On the discovery of two new monoclinic phases in the morphotropic phase boundary region of Pb[(Mg1/3Nb2/3)O3]- xPbTiO3 ceramics - Singh A.K.; Pandey D. (My University, 2025)
Profile analysis of powder x-ray and neutron diffraction data on (1-x)[Pb(Mg1/3-Nb2/3)O3]-xPbTiO3 (PMN-xPT) confirms the presence of two monoclinic phases with space groups Cm and Pm in the morphotropic phase boundary (MPB) region sandwiched by the rhombohedral and tetragonal phase fields. The phase transition sequence R-M B-O-MC-T predicted by Vanderbilt and Cohen for 3π/4 < β < 0.8π may indeed correspond to the composition dependent change of structure in the PMN-xPT system.